Adolescents' meaning-making experiences in physical education - in the transition from primary to secondary school - Mikalsen, Hilde Kristin; Lagestad, Pål Arild (Sport, education and society, 2020)
The aim of the study is to shed light on how physical education (PE) is experienced among a varied group of adolescents in school, and to nurture debate related to the relationship between adolescents' lived experience of PE and their identity-formation processes. Nuanced insights can help to increase teachers' ability to perceive, react to and deal appropriately in relation to fostering healthy lives in young people, in and through PE and physical activity (PA). The empirical material is derived from interviews with four adolescents, firstly in year 7, followed-up in year 8. Two of the teenagers were characterised by a high level of PA, two by a low level. The analysis was carried out using the interpretative phenomenological analysis method. The findings give a glimpse into the unique lived experience of PE of four pupils in modern society, and into how their meaning-making experiences of the subject seem to be situated in its context, as much as in wider contexts of family, and the PA related values, norms and discourses extant in their local communities. From their unique lived experiences of PE of the four participants, two overarching themes emerge. The first, 'PE is "a bag of sweets with more sweet than sour flavors", reflects the participants' experience and understanding of PE as predominantly positive. The second theme, 'PE is in negotiation with football culture', reflects that the culture of football, as a sport-related framework for the understanding of content and mastery, appears to have a special significance for the participants' meaning-making in physical education. Our findings also point to the importance of acknowledging that meaning making experiences in PE are embedded in the wider and overall context of the life of each individual.